The Influence of Compensation from Wages and Benefits on Healthcare Workers' Performance in Healthcare Services - Hakim, Jiddan Azizan; Maharani, Ghania Danisha; Wasir, Riswandy; Melani, Alif Indah; Arbitera, Cahya (Journal of Indonesian Health Policy and Administration, 2025)
This study aims to evaluate the influence of compensation, including wages, incentives, and benefits, on the performance of health workers in primary health centers and hospitals. A literature review was conducted using Google Scholar and PubMed, focusing on articles published in the last 5–10 years. From an initial search yielding 1,021 articles, nine were selected based on inclusion criteria. The results show that direct compensation (salary) and indirect compensation (benefits) have a positive impact on health worker performance. However, the effect of incentives varies depending on implementation. Motivation and job satisfaction were mediating factors that strengthened the relationship between compensation and performance. These findings highlight the need for fair, performance-based compensation systems to improve the productivity and retention of health workers in Indonesia.